2018
DOI: 10.3171/2016.11.jns161974
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglioma resection: a Surveillance, Epidemiology, and End Results (SEER) analysis

Abstract: OBJECTIVE The available evidence suggests that the clinical benefits of extended resection are limited for chemosensitive tumors, such as primary CNS lymphoma. Oligodendroglioma is generally believed to be more sensitive to chemotherapy than astrocytoma of comparable grades. In this study the authors compare the survival benefit of gross-total resection (GTR) in patients with oligodendroglioma relative to patients with astrocytoma. METHODS Using the Surveillance, Epidemiology, and End Results (SEER) Program (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 51 publications
1
30
1
Order By: Relevance
“…Stereotactic needle biopsy for diagnosis followed by systemic high-dose methotrexate-based chemotherapy is the current management paradigm for patients with PCNSL (9,10). Considering exquisite sensitivity to chemotherapy and the risk of postoperative morbidity in these patients, surgery is reported to play a limited role in PCNSL compared to the management of other intracranial tumors, like diffuse gliomas (11)(12)(13)(14). However, the widely adopted opinion of discouragement of surgery is based on some out-of-date retrospective studies with small samples (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic needle biopsy for diagnosis followed by systemic high-dose methotrexate-based chemotherapy is the current management paradigm for patients with PCNSL (9,10). Considering exquisite sensitivity to chemotherapy and the risk of postoperative morbidity in these patients, surgery is reported to play a limited role in PCNSL compared to the management of other intracranial tumors, like diffuse gliomas (11)(12)(13)(14). However, the widely adopted opinion of discouragement of surgery is based on some out-of-date retrospective studies with small samples (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Primary treatment is maximal safe resection, followed by radiotherapy and chemotherapy for highrisk patients [4,5]. Based on their chemosensitivity, it has recently been suggested that chemotherapy may be the optimal primary treatment for oligodendrogliomas [6].…”
Section: Introductionmentioning
confidence: 99%
“…The recently published SEER data on the association of GTR with improved survival in oligodendroglioma surprisingly showed no effect of surgery. 38 This finding might be due to the good sensitivity to chemotherapy with this diagnosis. However, despite the limitation of the missing molecular pathologic data like 1p19q codeletion, there is also a strong limitation based on the subjective assessment of EoR by the surgeons that is known to be usually overrated.…”
Section: Current Glioma Registriesmentioning
confidence: 81%